Potential study of Bera Lake water quality for alternative source of water supply - Nur Lyana Adibah, Mushiwan (2018)
This study concentrated on deciding potential of Bera Lake water quality for alternative source of water supply. Water quality is an important reference for describing the physical, chemical, and biological properties of water classification into each class. A study was conducted on physical, chemical, and biological parameter of Bera Lake on 2018 that contain water bodies at two stations with two sampling in two months of February and April 2018. Physical parameters were temperature and total suspended solids. Then, chemical parameters were pH value, dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), ammonia nitrogen, phosphorus and selected heavy metals such as zinc, copper, cadmium and lead. For biological parameter were Total Coliform and E. Coli. The water was classified based on Water Quality Index (WQI) and National Water Quality for Malaysia (NWQS). Based on WQI standard, classifications of water quality were based on type of class. After accomplishment the laboratory test, two stations in Bera Lake can being determined classified into class 2. Station 1 with 79.33 is for class 2, if use for water supply need conventional treatment. Station 2 with 79.24 also in class 2. If want to being as water supply the conventional treatment were needed. Overall, identifying water quality is important for differentiate suitable purpose of water body. It is very important for conserving and preserve source of surface water for water supply purposes in a future.